Analysis on the causes of cracking and excessive deflection of long span box girder bridges based on space frame lattice models. (April 2023) - Jin, Yongxue; Sun, Chenglin; Liu, Huifen; Xu, Dong
Abstract: Long-span prestressed concrete box girder bridges (continuous girder and rigid frame bridges) tend to have some apparent diseases. On the one hand, cracks in various directions appear in different positions of different slabs of the box girder; on the other hand, the deflection of the structure develops for a long time, which significantly exceeds the design expectation eventually. This paper intends to use the space frame lattice model, combined with the complete stress index system, to analyze the causes of cracks in different forms in an actual bridge. Unlike the single beam model and the transverse frame model under the guidance of the existing code system, the space frame lattice model that discretizes an entire box girder section into individual slabs can more precisely simulate the load that exceeds the code but exists. In addition, the complete stress index system enriches the design of box girder bridges and can well explain the cracking causes of old bridges. This paper also discusses the effect of the difference in creep and shrinkage caused by the difference in thickness among slabs on the deflection.